Combining material flow analysis with life cycle assessment to identify environmental hotspots of urban consumption. (20th July 2019) - Lavers Westin, Alexandra; Kalmykova, Yuliya; Rosado, Leonardo; Oliveira, Felipe; Laurenti, Rafael; Rydberg, Tomas
Abstract: Understanding the global environmental impacts of local consumption is an area of growing interest among policymakers and consumers. By knowing what products comprise urban consumption "hotspots, " municipalities and consumers alike could take deliberate actions to target and discourage consumption of high-impact products. In this paper, a new method for identifying environmental hotspots of consumption is presented. The main methodological advances are the following: i) material flow analysis of urban areas and life cycle assessment are combined; ii) a 16-year time-series of urban consumption data is used for selection of the most suitable representative products and for trend analysis; iii) representative products are selected systematically from consumption data of 1000 product types; iv) representative products are scaled up to represent consumption of the product groups; v) hotspots are identified by simultaneously evaluating six environmental impacts - acidification, climate change, eutrophication (marine and freshwater), photochemical ozone formation, and resource use; vi) for the case study, hotspots are connected to the city's profiles. The method was applied to the Swedish cities Stockholm, Gothenburg and Malmo and to Sweden in total. Electronics is a hotspot for all the studied areas and all the studied impacts and should be a prioritized product group for action. Fuel is a hotspot shared by all the areas while vehicles is a hotspot in Gothenburg. Meat is a nationwide hotspot, but not for the cities investigated. Gothenburg and Stockholm could collaborate to find effective measures for their common hotspot machinery. Thus, the method can be used to identify hotspots and find which product types could be part of national versus local programs. Highlights: Combined MFA-LCA environmental impact analysis of urban consumption. Region-specific analysis to identify need for local consumption reduction efforts. Some common but also different hotspots were identified for the studied areas. Method enables assessment of multiple environmental impacts simultaneously. Time series of consumption data allows for trend analysis.